Efektifitas Alat Bantu Pengambilan Keputusan (APBK) Guna Ketepatan Pengambilan Keputusan Ber-KB - Tri Iriyani; Nova Hikmawati; Yessy Nur Endah (LPPM Universitas Abdurrab, 2025)
Decision-making aids are tools that help optimize the counseling function and assist clients in selecting effective contraceptives. From the initial survey conducted by researchers, 7 of 10 respondents said they felt unsuitable for the contraceptive tools used because midwives did not use decision-making aids. The purpose of this study was to determine how well decision-making aids (ABPK) facilitate the right family planning decision-making in Sambirampak Lor Hamlet, Kotaanyar District. This study used an analytical survey design with a cross-sectional approach. The population in this study were all family planning acceptors, the sampling technique used proportional stratified random sampling, namely 40 respondents. The data used were primary data collected using questionnaires, with univariate and bivariate data analysis and analysis tested using Wilcoxon. Cadres must mobilize women of childbearing age to increase awareness of fertile women about the importance of family planning through peer groups.